Subspecies and Distribution. A.a.alcesLinnaeus,1758—fromScandinavia,Finland,BalticstatesandPolandEtotheYeniseyRiver. A.a.americanaClinton,1822—ECanada(COntariotoNewfoundland). A.a.andersoniPeterson,1950—fromBritishColumbiatoMinnesotaandOntario. A.a.buturliniChernyavsky&Zhelesnov,1982—NESiberiaandKamchatka. A.a.cameloidesMilne-Edwards,1867—NMongolia,Ussuriland,NManchuria. A.a.gigasMiller,1899—AlaskaandYukon. A.a.pfizenmayeriZukowsky,1910—fromCSiberiatoStanovoyMtsandCherskiyMts. A. a. shirasi Nelson, 1914 — from S Alberta to Wyoming and Utah. in Cervidae - Don E. Wilson; Russell A. Mittermeier (Lynx Edicions, 2011)
Subspecies and Distribution. A.a.alcesLinnaeus,1758—fromScandinavia,Finland,BalticstatesandPolandEtotheYeniseyRiver. A.a.americanaClinton,1822—ECanada(COntariotoNewfoundland). A.a.andersoniPeterson,1950—fromBritishColumbiatoMinnesotaandOntario. A.a.buturliniChernyavsky&Zhelesnov,1982—NESiberiaandKamchatka. A.a.cameloidesMilne-Edwards,1867—NMongolia,Ussuriland,NManchuria. A.a.gigasMiller,1899—AlaskaandYukon. A.a.pfizenmayeriZukowsky,1910—fromCSiberiatoStanovoyMtsandCherskiyMts. A. a. shirasi Nelson, 1914 — from S Alberta to Wyoming and Utah. Published as part of Don E. Wilson & Russell A. Mittermeier, 2011, Cervidae, pp. 350-443 in Handbook of the Mammals of the World – Volume 2 Hoofed Mammals, Barcelona :Lynx Edicions on page 431, DOI: 10.5281/zenodo.6514377